Implementasi Program Pelayanan Berkelanjutan Inseminasi Buatan Dan Gangguan Reproduksi Sapi Pada Dinas Peternakan Dan Perkebunan Kabupaten Pinrang - Makmur, Andi Nurfadilah; Parawangi, Anwar; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2021)
ABSTRACTThis study purposed to find out the implementation of the Sustainable Service program for Artificial Insemination and Cattle Reproduction Disorders at the Livestock and Plantation Service Office of Pinrang Regency. This study used qualitative methods by conducting data collection techniques through observation and interviews. The data obtained from the research results were examined using data reduction techniques, data presentation, and making conclusions. The results showed that the aspects of (1) communication with the formation of an insemination service team that always coordinated with each other in determining the program implementation strategy. (2) The service team consisted of experts who were competent in handling insemination for resources in implementing artificial insemination and reproductive disorders. (3) Disposition was the attitude of the implementers of artificial insemination and reproductive disorders services who were truly committed to carrying out insemination activities by always conducting deliberations in carrying out. (4) the bureaucratic structure could be seen from the division of labor of each insemination service team so that the implementation of services was carried out in stages.Keywords: Policy implementation, artificial insemination, and animal husbandry